Generation of six human iPSC lines from patients with a familial Alzheimer's disease (n = 3) and sex- and age-matched healthy controls (n = 3) - Raska, Jan; Hribkova, Hana; Klimova, Hana; Fedorova, Veronika; Barak, Martin; Barta, Tomas; Pospisilova, Veronika; Vochyanova, Simona; Vanova, Tereza; Bohaciakova, Dasa (Stem cell research, 2021)
Human induced pluripotent stem cell (iPSC) lines were generated from primary human fibroblasts isolated from three patients with a familial form of Alzheimer's disease (AD) and three healthy control individuals. Two AD-iPSC lines carry a PSEN1 mutation A246E; the third cell line carries a PSEN2 mutation N141I. The fibroblasts were reprogrammed with Yamanaka factors (OSKM) using a commercially available Epi5 Reprogramming Kit. The pluripotency of iPSCs was confirmed by the expression of pluripotency factors and by their ability to differentiate to all three germ layers in vitro. Newly derived cell lines can be used to model Alzheimer's disease in vitro.
Keywords: buněčné linie; buněčná diferenciace; Cell Line; Alzheimerova nemoc; Alzheimer Disease; fibroblasty; indukované pluripotentní kmenové buňky; mutace; lidé; Mutation; Fibroblasts; Humans; Cell Differentiation; Induced Pluripotent Stem Cells